Applications and Prospects of CRISPR/Cas9-Mediated Base Editing in Plant Breeding - Li, Yizhen; Liang, Jing; Deng, Bufang; Jiang, Yingli; Zhu, Jingyan; Chen, Like; Li, Min; Li, Juan (Current Issues in Molecular Biology, 2023)
The clustered regularly interspaced short palindromic repeats (CRISPR)/associated protein 9 system (Cas9) has been used at length to optimize multiple aspects of germplasm resources. However, large-scale genomic research has indicated that novel variations in crop plants are attributed to single-nucleotide polymorphisms (SNPs). Therefore, substituting single bases into a plant genome may produce desirable traits. Gene editing by CRISPR/Cas9 techniques frequently results in insertions–deletions (indels). Base editing allows precise single-nucleotide changes in the genome in the absence of double-strand breaks (DSBs) and donor repair templates (DRTs). Therefore, BEs have provided a new way of thinking about genome editing, and base editing techniques are currently being utilized to edit the genomes of many different organisms. As traditional breeding techniques and modern molecular breeding technologies complement each other, various genome editing technologies have emerged. How to realize the greater potential of BE applications is the question we need to consider. Here, we explain various base editings such as CBEs, ABEs, and CGBEs. In addition, the latest applications of base editing technologies in agriculture are summarized, including crop yield, quality, disease, and herbicide resistance. Finally, the challenges and future prospects of base editing technologies are presented. The aim is to provide a comprehensive overview of the application of BE in crop breeding to further improve BE and make the most of its value.